PENGARUH VISUAL THINGKING STRATEGY IN AUGMENTED REALITY DALAM MEMFASILITASI KETERAMPILAN PEMECAHAN MASALAH - M. Fauzan Abdillah; Saefullah, Asep; Guntara, Yudi (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study proposes the Visual Thinking Strategy in Augmented Reality (ViTSAR) application, which combines E-modules, LKPD, and interactive media. The approach used in this study is quantitative with a Pretest-Posttest Nonequivalent group design. The population used in this study were students of class XII MIPA. While the sample to be used in this study consisted of class XII MIPA 3 as the experimental class and XII MIPA 5 as the control class at SMAN 1 Baros. This study used a problem-solving skills test instrument in the form of a description and a student response questionnaire instrument. Data analysis was conducted using descriptive statistics T-test to determine the effect of ViTSAR learning media on the experimental and control classes. The results of the hypothesis test showed that the value of Tcount = 5,700 was greater than Tcount = 2,447, so there was a difference in the mastery of problem-solving skills of the experimental class and the control class on the Gauss law material.